2014
DOI: 10.1002/acr.22199
|View full text |Cite
|
Sign up to set email alerts
|

Decline in Hand Bone Mineral Density Indicates Increased Risk of Erosive Change in Early Rheumatoid Arthritis

Abstract: Objective. Despite better disease suppression with combination disease-modifying antirheumatic drugs (DMARDs), some patients with rheumatoid arthritis (RA) have progressive erosive disease. The objective of this study was to determine whether hand bone mineral density (BMD) loss in the first 6 months of treatment indicates increased risk of erosions at 12 months. Methods. Patients with DMARD-naive early RA receiving treat-to-target therapy were studied (n ‫؍‬ 106). Hand BMD was measured at baseline and 6 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 26 publications
3
15
0
Order By: Relevance
“…Our data in AIA rats confirmed some clinical results performed only in early RA, where bone loss in metacarpal heads (MCH) was associated with high risk of erosive disease, assessed with 2D imaging (Black et al, ; Wevers‐de Boer et al, ). By using high‐resolution peripheral quantitative CT in humans, reproducible analysis of bone microarchitecture was proposed in RA (Barnabe and Feehan, ).…”
Section: Discussionsupporting
confidence: 86%
“…Our data in AIA rats confirmed some clinical results performed only in early RA, where bone loss in metacarpal heads (MCH) was associated with high risk of erosive disease, assessed with 2D imaging (Black et al, ; Wevers‐de Boer et al, ). By using high‐resolution peripheral quantitative CT in humans, reproducible analysis of bone microarchitecture was proposed in RA (Barnabe and Feehan, ).…”
Section: Discussionsupporting
confidence: 86%
“…Similar observations have also been reported in patients with early RA [ 30 ], suggesting an association between disease activity and bone loss. Hand BMD loss has also been shown to indicate an increased risk of erosive disease [ 10 , 11 , 31 , 32 ]. Data from an observational study demonstrated that BMD loss at 6 months was associated with higher erosion scores, and a higher proportion of patients with BMD loss at 6 months had at least one erosion and a higher risk of erosion progression at 12 months [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…A longitudinal study of 50 patients with early RA (whose hand BMD was measured at baseline, 6 and 12 mo) indicated that the baseline value of hand BMD was associated with radiographic scores at 12 mo [101]. Another longitudinal study consisting of 64 patients with RA confirmed the predictive value of hand BMD loss in the first year for the subsequent radiographic progression (6.4 year follow up) [103]. A longitudinal study by Black et al [104] showed hand BMD loss in the first 6 mo might be a predictor for erosions at 12 mo.…”
Section: Relationship Of Bone Mineral Density (Bmd) and Different Artmentioning
confidence: 97%